(untitled) (Global Journal of Management and Business Research, 2018)
The most important thing of everyone life and work is satisfaction. This study is conducted to analyze the job satisfaction among the female teachers of government colleges of Rangpur City in Bangladesh. Normally job satisfaction is considered as a factor of social psychology but in this study job satisfaction is analyzed from organizational perspective. The objectives of this study is to understand the indicators of female teachers job satisfaction, to find out the satisfaction level of the female teachers, to find out the reasons behind the job dissatisfaction and to give some recommendations in the relevant area. To fulfill this aims data are collected from the female teachers of the Government colleges in respective area. The purposive random sampling has been used and the sample size range is 50. A well set questionnaire that includes some of demographic and mostly scale based questions to collect the data, analyzed it by using some common statistical tools. The empirical study has found some factors which affect job satisfaction of female teachers; these are salary, security, college reputation, maternity leave, housing facility, transport facility etc.